2011
DOI: 10.1007/s12192-010-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of soluble Hsp70 is associated with vascular calcification

Abstract: It has been previously reported that serum levels of 70-kDa heat shock protein (Hsp70) are elevated in peripheral artery disease. The aim of the present study was to examine whether increased serum Hsp70 levels are related to the extent of arterial calcification and standard laboratory parameters of patients with peripheral artery disease, as well as to markers of inflammation (C-reactive protein), atherosclerosis (homocysteine), and calcification (fetuin-a). One hundred eighty chronic atherosclerotic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 55 publications
2
24
1
Order By: Relevance
“…Mast cells, dendrite cells, and even tumor cells had also been observed to be a source of circulating HSP70s (Laulagnier et al 2004;Mambula and Calderwood 2006). Our result of elevated plasma HSP70 is consistent with the data from Krepuska (Krepuska et al 2011) and Wright (Wright et al 2000), which showed an increased level of serum HSP70 (HSPA1A) in atherosclerosis patients, but is in contrast to other reports showing a lower concentration of circulating HSP70 (HSPA1A) in atherosclerotic subjects (Dulin et al 2010;Galovic et al 2016). The reasons for this conflict have not been fully understood, but perhaps the differences in the models and species may contribute to explain the contrasting findings.…”
Section: Discussionsupporting
confidence: 92%
“…Mast cells, dendrite cells, and even tumor cells had also been observed to be a source of circulating HSP70s (Laulagnier et al 2004;Mambula and Calderwood 2006). Our result of elevated plasma HSP70 is consistent with the data from Krepuska (Krepuska et al 2011) and Wright (Wright et al 2000), which showed an increased level of serum HSP70 (HSPA1A) in atherosclerosis patients, but is in contrast to other reports showing a lower concentration of circulating HSP70 (HSPA1A) in atherosclerotic subjects (Dulin et al 2010;Galovic et al 2016). The reasons for this conflict have not been fully understood, but perhaps the differences in the models and species may contribute to explain the contrasting findings.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with prior studies (Pockley et al 2003, Zhu et al 2003, Martin-Ventura et al 2007, Armutcu et al 2008, and it has been discussed in our previous publication (Dulin et al 2010). In contrast to these works, Zhang et al (2010) reported that high extracellular Hsp70 levels were associated with the increase and the severity of acute coronary syndrome (ACS), and recently, it has been reported that serum Hsp70 levels correlate with the severity of atherosclerosis in patients with peripheral artery disease of the lower extremities and carotid artery disease (Krepuska et al 2011). The discrepancy between the results of the different studies could have been due, as the authors propose, to differences in population characteristics, the difference of samples (serum versus plasma), and different kinds of ELISA used.…”
Section: Discussionsupporting
confidence: 91%
“…Survival was plotted according to the Kaplan-Meier method, and differences in survival between the groups were compared with the log-rank test. The power of the logrank test was sufficiently high (p=0.9, alpha=0.05) to support the above conclusion HSP70 in the progression of vascular calcification was also demonstrated: its levels correlated with the severity of atherosclerosis in patients with carotid artery disease and chronic lower limb ischemia (Krepuska et al 2011).…”
Section: Introductionmentioning
confidence: 55%